Pocket companion to Robbins pathologic basis of disease (Saunders, 1999)
The subjects of cellular injury and cellular death, acute and chronic inflammation and repair, formerly presented and expanded into four chapters. The disorders of the female genital tract and breast formerly discussed in one chapter, have now been devided into separate chapters,...